(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article deals with the phonetic-phonological status of the interdental consonants [n], [l] and [t], in the Mapudungun spoken in the Coastal area of the Huapi Island, IX Region of Araucania. After analyzing minimal pairs, quantification of interdental segments versus alveolar [n], [l] and [t], and the phonological awareness of the assessed speakers, the validity of these segments could be concluded both as phones and as phonemes. That is to say, /n/, /l/ y /t/; y /n/, / l /and /t/, are phonemes in this area.